The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1126/science.1233009
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Non- NF2 Meningiomas Reveals Mutations in TRAF7 , KLF4 , AKT1 , and SMO

Abstract: We report genomic analysis of 300 meningiomas, the most common primary brain tumors, leading to the discovery of mutations in TRAF7, a proapoptotic E3 ubiquitin ligase, in nearly one-fourth of all meningiomas. Mutations in TRAF7commonly occurred with a recurrent mutation (K409Q) in KLF4, a transcription factor known for its role in inducing pluripotency, or with AKT1E17K, a mutation known to activate the PI3K pathway. SMO mutations, which activate Hedgehog signaling, were identified in ~5% of non-NF2 mutant me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
643
3
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 734 publications
(742 citation statements)
references
References 32 publications
31
643
3
5
Order By: Relevance
“…Zhu et al (2009) showed that in primary cortical neuron cultures, KLF4 overexpression induced the activation of caspase-3 in response to glutamate excitotoxicity. In a recent Science paper, Moore et al detected no differences in survival between KLF4-and controltransfected hippocampal neurons, although KLF4 suppresses axon and dendrite initiation and elongation in this system (Clark et al 2013). Our data presented herein support the conclusion that KLF4 is an antiapoptotic factor.…”
Section: Discussionsupporting
confidence: 81%
“…Zhu et al (2009) showed that in primary cortical neuron cultures, KLF4 overexpression induced the activation of caspase-3 in response to glutamate excitotoxicity. In a recent Science paper, Moore et al detected no differences in survival between KLF4-and controltransfected hippocampal neurons, although KLF4 suppresses axon and dendrite initiation and elongation in this system (Clark et al 2013). Our data presented herein support the conclusion that KLF4 is an antiapoptotic factor.…”
Section: Discussionsupporting
confidence: 81%
“…77 In this regard, clinical correlation with the rapidly accumulating genetic data on meningiomas will certainly also help to tailor treatment recommendations for Grade II and III meningiomas. 7,14,15 conclusions This study reviews reported management strategies and outcomes for patients with WHO Grade II and III meningiomas in an effort to develop a logical algorithm for evidence-based treatment recommendations. The evidence primarily supports safe GTR of AMs or, if GTR is not feasible, STR with adjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, either AKT1 or β-catenin mutation in malignant tumors usually co-occurs with other driver genomic alterations (22,30,31). However, AKT1 mutations in benign tumors, such as meningiomas and PSHs, and β-catenin mutations in pilomatricoma do not usually co-occur with each other or other known driver mutations (32)(33)(34). It is possible that AKT1 or β-catenin mutation alone is able to produce a benign tumor but not a malignant tumor.…”
Section: Discussionmentioning
confidence: 99%